Multilevel and Spatially Heterogeneous Factors Influencing Poor Households’ Income in a Frontier Minority Area in Northeast China - Binyan Wang; Mark W. Rosenberg; Shijun Wang; Peifeng Yang; Junfeng Tian (Complexity)
Increasing the income of poor rural households is essential for the realization of China’s goal of sustainable development, which entails inclusive and equitable development and reducing the developmental gap between urban and rural areas. We conducted a case study of Wangqing County, a frontier minority area in Northeast China to examine spatial patterns and income differentials among poor rural households in this area. We quantified existing associations between household-level and environmental-level characteristics and income by applying hierarchical linear models. We subsequently applied Geographically Weighted Regression to analyze the spatial heterogeneity of the environmental-level variables and develop an understanding of the interaction mechanism of influencing factors. The results revealed that the distribution of villages, where income levels were similar, showed significant spatial agglomeration characteristics. Our findings also provide empirical evidence that household- and village-level characteristics together determine the income of poor households, but that household-level characteristics determine destitution to a greater extent than environmental characteristics. More specifically, the sex, health condition, and labor capacity of the household head, household size, the dependency ratio, social welfare, and off-farm work are significantly associated with household income. At the environmental level, arable land, the distance to the county center, and the average altitude had spatially heterogeneous impacts that varied in direction and intensity. This systematic study provides a more comprehensive and integrated understanding of the factors influencing the income of poor households in a frontier minority area in Northeast China.